(3GSJjLeGs (3MdbGJ faSjI jbOegG GdeQjV GdfaSjs - (3gGTe, eMeO aDGOs; (3LeGd, fgGds; (3YHO Gddg, YjSis; (3Ydj, eYJR MSfjfs ((3GdbGgQIs (3GdSQGL ddfTQ hGdJhRjYs, 2024)
(3jYGfj hGMlO ef cd CQHYI CTNGU peqfG cd YGme pef eTcdI JJYdb HUMJg GdfaSjI Ch GdYbdjI, hjJaQO Gdbdb hGdGcJFGH nhMOge HEUGHI CcKQ ef (B500 (3edjhf TNU Mhd GdYGde(B. (3deGPG JfJTQ Jdc GdeTcdGJ Ydi gPG GdfWGb GdhGSY? heG gh GdCeQ GdPj jLYd MjGJfG GdeYGUQI dgG gPG GdJCKjQ aj UMJfG GdfaSjI hGdYbdjI? hdne dG jRGd gfGc GdcKjQ ef GdGdJHGS Mhd gPg GdbVGjG? hdeGPG de ffac HYO Yf GdhUeGJ GdJj JdMb GdMOjK Yf eKd gPg GdehGVjY?s
(3gPG GdfU eJQLe Edi GddZI GdYQHjI ef GddZI GdEfLdjRjIs
Keywords: (3GdCeQGV GdYbdjIs; (3GdUMI GdYbdjIs; (3GdUMI GdfaSjIs